Tinjauan Hukum Islam Tentang Mekanisme Transaksi E-Wallet - Sunarsa, Sasa; Fauzi, Ilham Nurul (Jurnal Hukum Ekonomi Syariah, 2023)
Digital transactions or e-wallets are payment systems made online where sellers and buyers transact online to offer convenience for their users. Currently in Indonesia, digital wallets or electronic money are one of the non-cash payment instruments used in transactions via the internet or commonly called e-wallet transactions. However, the e-wallet transaction mechanism is indicated not in accordance with the principles of Islamic law. The research questions in this problem are: 1. What is the mechanism of e-wallet transactions? 2. How does Islamic law review the mechanism of e-wallet transactions? So the objectives of this study are: 1. To find out the mechanism of e-wallet transactions. 2. To know the review of Islamic law on the mechanism of e-wallet transactions. The method used in this study is field research. This research uses descriptive methods and analysis with a qualitative approach. In the implementation of this study, the author used data collection techniques by observation, interviews, and documentation. The results of the study can be concluded that from the e-wallet transaction mechanism from the perspective of Islamic law, the type of cooperation agreement between the company and the merchant is wakalah, the type of contract in the top-up mechanism is sharf, the type of contract on the deposit is wadiah yad amanah, and wadiah yad dhamanah, and also the type of contract on the transaction, namely bai, ijarah, and qardh, then in accordance with the fatwa dsn-mui, which is as long as it does not conflict with Islamic law as long as it does not contain elements of usury,  Gharar, Maysir, and Israf.  Keywords: E-Wallet, Transaction, Islamic Law